THE EFFECT OF COMPANY SIZE, COMPANY AGE, OWNERSHIP CONCENTRATION, LEVERAGE, AUDIT COMMITTEE, AND COMPANY PERFORMANCE, ON INTELLECTUAL CAPITAL DISCLOSURE - Icih Icih; Putri Utami Permata Hati (JASS (Journal of Accounting for Sustainable Society), 2021)
This study aims to determine the effect of firm size, firm age intellectual capital disclosure. The population used in this study are companies listed on the Indonesia Stock Exchange in 2017-2019. This study uses purposive sampling method for determining the sample. The method of analysis, ownership concentration, leverage, audit committee and company performance used in this study is multiple regression analysis with SPSS version 22 for windows program. The population in this study are all financial companies, totaling 94 companies listed on the Indonesia Stock Exchange, the number of financial companies sampled is 53 companies for 3 years of observation. Partially, the results of this study indicate that only the size of the company has an effect on the disclosure of intellectual capital. Meanwhile, firm age, ownership concentration, leverage, audit committee, and firm performance have no effect on intellectual capital disclosure. Simultaneously, the results of this study indicate that firm age, concentration of ownership, leverage, audit committee, and firm performance have a simultaneous effect on intellectual capital disclosure.